<h3>

**Answer is 3**</h3>

=====================================================

Work Shown:

x = some unknown number

x+12 = adding 12 to the unknown number

4(x+12) = multiplying the previous sum by 4

4(x+12) = 60 .... set this equal to the desired result we want

Now solve for x. We will undo the steps done above to isolate x

----------------

4(x+12) = 60

x+12 = 60/4 .... divide both sides by 4 to undo "multiply by 4"

x+12 = 15

x = 15-12 .... undo "add 12" by subtracting 12 from both sides

x = 3

-----------------

The unknown number is 3

add 12 to it to get 3+12 = 15

multiply that sum by 4 to get 15*4 = 60

Answer is confirmed.

**Answer: 216**

**Step-by-step explanation:**

**Answer:**

-27

**Step-by-step explanation:**

just did it

**Answer:**

**Step-by-step explanation:**

x=

−b±√b2−4ac

2a

x=

−(−13)±√(−13)2−4(1)(5)

2(1)

x=

13±√149

2

x=

13

2

+

1

2

√149 or x=

13

2

+

−1

2

√149

**Answer:**

28

**Step-by-step explanation:**

4 x 7 = 28

Hope this helps you :)